Laser Treatment in oral Cavity Soft Tissue in Pediatrics; Current Knowledge and Future Directions - Shahoon , Hossein; Rafighi , Ali; Ashrafi , Mehdi; Ebrahimi , Hossein; Mozafar, Sedighe (Galen Medical Journal, 2024)
This review explores the advancements in laser therapy for pediatric oral cavity soft tissue problems, highlighting its therapeutic implications and advantages over conventional treatments. The research began with a comprehensive literature search in December 2023, identifying 159 articles related to laser treatments in pediatric dentistry. After eliminating duplicates, 84 distinct articles were analyzed, leading to the selection of 5 relevant studies. The findings indicate that low-level laser therapy (LLLT) offers significant benefits, including enhanced wound healing, pain relief, and reduced postoperative complications such as bleeding and infection. Various laser types, including Er:YAG, CO2, and diode lasers, have shown effective clinical outcomes in procedures like frenectomy and gingival re-contouring. Notably, LLLT’s non-invasive nature minimizes edema and inflammation, making it particularly suitable for young patients who may be anxious about dental procedures. The review emphasizes that lasers can be utilized as either primary or supplementary tools in both surgical and non-surgical interventions, leading to improved patient experiences and outcomes. Furthermore, the paper discusses the importance of understanding the physical principles of laser therapy, as different wavelengths interact uniquely with various tissues, influencing treatment efficacy. Overall, this review advocates for the judicious application of laser technology in pediatric dentistry, aiming to enhance treatment outcomes and patient satisfaction while addressing the challenges associated with traditional methods.